Timing detectors setup prototype for determining EAS axis direction - Kalikulov, O.A.; Saduyev, N.O.; Shaulov, S.B.; Sedov, A.N.; Oskomov, V.V.; Yerezhep, N.O.; Baktoraz, A.Y.; Utey, Sh.B.; Zhumabayev, A.I.; Mukhamejanov, Y.S.; Shinbulatov, S.K. (Recent Contributions to Physics, 2021)
This work presents a prototype setup for determining extensive air showers (EAS) axis direction. The detector system consists of four scintillation detectors (100x100x1 cm) using wavelength-shifted fibers light collection. This prototype will make it possible to create system of detectors with fast timing (timing detectors) and supplement the complex shower installation, located at 3340 m above sea level at the Tien Shan High-altitude Scientific Station (TSHSS) near Almaty, Kazakhstan. A method for determination the direction of extensive air showers is described. It is indicated that to assess the determination of extensive air showers direction, it is necessary to define azimuth and zenith angles with required accuracy. In this work, calibration of detectors with vertical cosmic muons is presented. To calibrate the detectors, a test bench was assembled, and its schematic representation is shown. The signals from scintillation detectors were analyzed using a CAEN DT 5725 8-channel analog-to-digital converter. In addition, there is a discussion of the preliminary results from calibration. Single-particle calibration of detectors will allow estimating the number of particles passed through the scintillation detector.